XMU-MP-1 attenuates osteoarthritis via inhibiting cartilage degradation and chondrocyte apoptosis - Hao, Xue; Zhao, Jing; Jia, Liyuan; He, Ting; Wang, Huanbo; Fan, Jing; Yang, Yating; Su, Fei; Lu, Qingda; Zheng, Chao; Yang, Liu; Jie, Qiang (Frontiers in Bioengineering and Biotechnology, 2022)
Osteoarthritis (OA) is the most prevalent type of degenerative joint disease; it is reported to be associated with inflammatory responses, chondrocyte apoptosis, and cartilage degeneration. XMU-MP-1 is a selective MST1/2 inhibitor which activates the downstream effector YAP and promotes cell growth. It has displayed excellent benefits in mouse intestinal repair, as well as liver repair and regeneration. However, the effects of XMU-MP-1 on OA remain unclear. In this study, we investigated the therapeutic role of XMU-MP-1 on interleukin-1β (IL-1β)-induced inflammation in mice chondrocytes and the destabilization of the medial meniscus surgery (DMM)-induced OA model. In chondrocytes, treatment with XMU-MP-1 elevated the matrix metalloproteinases (Mmp3, Mmp13) and decreased the extracellular matrix (Col2, Acan) induced by IL-1β. Moreover, XMU-MP-1 strongly inhibited IL-1β-induced chondrocyte apoptosis and significantly promoted chondrocyte proliferation. Furthermore, XMU-MP-1 demonstrated a protective and therapeutic influence on the mouse OA model. These findings indicate that XMU-MP-1 may have a protective effect on cartilage degradation and may be a new potential therapeutic option for OA.